Marital conflict management model based on the Imam Al-Ghazali approach - Zaiton Ismail
The instability of marriage and family institutions in the contemporary societies is unseen before. Muslim marriages are met with the same fate whereby statistics of divorces are indeed alarming. With such situation, the essence of this study is to develop a theory that connects with conflict, coping and resolution and explains how young couple facing difficulties in their marital relationships. The theory thus developed, is in line with the cultural values and belief system of this particular population. The study employed qualitative research design, using grounded theory methodology. Through purposive sampling, seven (7) married individuals having affiliation to Muslim based NGO, living in Kuala Lumpur were selected. The data was collected through interviews and whatapps (WA) conversation with the participants. The verbatim transcription of the data was managed using ATLAS.ti software version 1.0.48 (123). The grounded theory process of data analysis was employed, starting with open coding, axial coding, and selective coding (Strausss & Corbin, 1990, 2008). The data from the experiences of Muslim participants and the elements of marital well-being from the perspective of al-Ghazali were integrated to form a model i.e. Muslim Application of Value System in Marital Conflict (MAVSMC). The model generated showed that their process of conflict resolving involves prevention of aggravation of conflict in relationship and use of Qur'anic remedies. The process that started with the generation of the conflict, followed by experiencing conflict, coping with the conflict and finally managing and resolving conflict brought the outcome of resolving the conflict. The model is recommended to be integrated into pre-marriage courses, training of counsellors and guidance officers at religious departments and other helping professionals particularly those who are involved in marital counselling. Further research should consider quantitative and mix method design to enhance the knowledge and skills for building a prevention and therapeutic module for marital conflict management.